Welfare Perceptions of the Youth: A Turkish Case Study - Bilal Bagis; Aynur Yumurtaci (Global Labor Organization (GLO), 2020)
Despite little to no academic attention, widespread perception of the welfare state policies is a critical aspect of its evaluation, existence and the validity processes; especially that amongst youth and the new generations. This paper discusses welfare or the quality of life perceptions in Turkey and in particular the university students' economic and social welfare concerns. The paper is based upon survey outcomes from two different cities' university students, across Turkey; and analyzes the Turkish university students' current welfare, happiness, contentment with life and the future financial wellness perceptions. We employ the standard chi-square test of independence to test our hypotheses. The research aims to contribute to the efforts towards a roadmap regarding the socio-economic policies to be implemented for the future of Turkey. The paper finds growing financial concerns among university students in terms of social and economic welfare. This is despite the recent economic, social and cultural transformation in modern Turkey. Meanwhile, the latest pandemic is likely to have deteriorated these perceptions. This research, meanwhile, is a worthy analysis to understand contentment regarding the current economic outlook, as well as the concerns and confidence in terms of financial future and wellness. Understanding these perceptions may potentially help in carving the middle and long-term national social and economic policies.
Keywords: E6; E71; I3; P46; 330; Welfare; Welfare perceptions; Financial well-being; Turkish economy; Social policy